"Probabilidades negativas" e tomografia de Qubits - Silva, Alcenísio José de Jesus (Universidade Federal de São Carlos, 2007)
In this dissertation we approached the tomography of discrete systems, understood as the representation and the reconstruction of states. For the tomography we used distribution functions of symmetrical pseudo-probabilities. The coefficients of the distribution function of "probabilities" are "joint probabilities", that eventually can be negative, associated to incompatible observables. The "negative probabilities" contains not only information about the measurements of counts, but also on the quantum state of the systems. We present the argument of Scully, Walther and Schleich that uses double slit interference to give a meaning to the "negative probabilities" and we propose one alternative example using beam splitters and an single photon. Like this, moreover we define distribution functions based in generalized quantization axes for any directions, we present the physical interpretation of the resulting "negative probabilities". We showed the reason because all explanation usually done to justify "negative probabilities" seems to be contradictory and are not convincing. Is the interpretation of the "negative probabilities" that retain the heart, not only of the present work, but also, of the whole Quantum Mechanics, its only mystery, as Feynman says
Keywords: Probabilidade negativa; Tomografia de Qubits.; CIENCIAS EXATAS E DA TERRA::FISICA